Analisis Tingkat Kepatuhan Wajib Pajak Hotel di Kecamatan Rantepao - Jevita Joni; Marinus Ronal; Marchelin (MES Bogor, 2024)
This research aims to analyze the level of hotel tax compliance in Rantepao District. This research aims to analyze the level of hotel tax compliance in Rantepao District. The research method used is a quantitative method with a sample of 4 hotels with the results of this research. This research shows that the level of hotel tax compliance in Rantepao District varies, with the majority of hotels showing good compliance, 75% of the hotels sampled in this research are categorized as compliant taxpayers because they fulfill their tax obligations well, demonstrate conformity of reporting, timeliness of payments, and completeness of dokuments in accordance with regulations and 25% are categorized as non-compliant taxpayers possibly due to a lack of understanding of the importance of tax comlpiance.